A novel optimization approach for bonded tubular gap K-joints made of FRP composites. (December 2020) - Bharti, Kundan; Kumaraswamidhas, L.A.; Das, R.R.
Abstract: Composite structures have wide applications in mechanical and civil-structures due to low weight-to-strength ratio. Such structures consist of several joints, which may run a risk of eventually weakening a structure around the joint region, particularly in case of excessive weight. It is, therefore, necessary to design the structures and optimize their geometric parameters to limit the chances of failures. The present study focuses on the laminated FRP composite made bonded tubular gap K-joint (α = 30°) with triangular adhesive fillet under axial compressive loading. The modeling and analysis were conducted by using the Finite Element (FE) based software ANSYS. The aim of this study is to optimize the different joint parameters, based on a failure criteria and ply-stacking sequence. The modeling procedure was validated with available experiment records and Finite Element Method (FEM) results. The geometric parameter tc  = 6.0 mm tb  = 4.4 mm and fr  = 24.49 were taken with the help of the failure criteria, and also an empirical equation was suggested to predict the failure index. These parameters were further optimized using the Genetic Algorithm (GA) and reduce the failure index up to 20.0% and 23.8% for Bottom Toe Line (BTL) and Top Toe line (TTL) respectively. Finally the minimum value of the failure index was obtained by using the different ply stacking sequence and cross-ply stacking sequence gives the minimum value of failure index at BTL as well as TTL.